KINERJA STIFFNESS, FATIGUE, DAN CREEP CAMPURAN ASPAL PANAS ASPHALT CONCRETE WEARING COURSE (AC-WC) - Thanaya, I Nyoman Arya; Ariawan, I Made Agus; Putra, I Made Debby Surya Adi (JURNAL SPEKTRAN; Vol 8 No 1 (2020): VOL. 8, NO. 1, JANUARI 2020, 2020)
Damage type that common happens to Asphalt Concrete Wearing Course (AC-WC) is the crack due to fatigue.  This research objective is to analyze the performance of the stiffness, fatigue, static creep and dynamic creep of the AC-WC hot asphalt mix to optimum asphalt content.  The research was conducted at Road Laboratory of the Civil Engineering Department, Udayana University.  The mixture was produced in hotmix and tested with Marshall procedure.  The method used in testing stiffness, fatigue and creep testing refers to the British Standard.  The equipment that is used is the Dynapave UTM 30. Based on the research it was found out that the optimum asphalt content (OAC) of AC-WC mix was 6.05%.  The ITSM value at temperature of 10 o C, 20 o C, 30 o C were 6175 MPa, 4356 MPa, 3790 MPa, respectively.  The fatigue performance on dynamic loading at pressure of 300 kPa failed at 37,401 times of load repetition, at pressure of 500 kPa failed at 15,513 times of load repetition, at pressure of 700 kPa failed at 3,866 times of load repetition.  The static creep performance was 20.84 MPa.  The stiffness of creep dynamic was 13.69 MPa.  In general comparison, between the test result of the static creep and dynamic creep shows that with dynamic load the sample gave bigger strain so its stiffness becomes smaller, compared to the static load.  In other words, the dynamic load causes bigger deformation.